KONSEP RESTORATIVE JUSTICE TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM - Sumaidi Sumaidi (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
In case handling children known adanyakonsep Restorative Justice, which is handling the concept of Conflict Child Law, involving all stakeholders, including the actors themselves. In Restorative Justice approach to crime is not only matamasalah law violations that harm society, but also detrimental to itself. Restorative Justice is a paradigm that puts the child case management efforts outside the formal judicial process. Not that remove errors actors, Justrusyaratnya, no admission of guilt from the perpetrator and the victim to forgive, Restorative Justice can be regarded as an effort to meet the principle of criminal law concerning children: "ultimum remidium" jail is the worst step for the disposal of the child, Restorative Justice enacted in crime mild or prohibited acts that did not result in permanent loss.Keyword : concept, restorative, justice